Between Conspiracy Beliefs, Ingroup Bias, and System Justification: How People Use Defense Strategies to Cope With the Threat of COVID-19 - Jutzi, Chiara A.; Willardt, Robin; Schmid, Petra C.; Jonas, Eva (Frontiers in Psychology, 2020)
The current situation around coronavirus disease 2019 (COVID-19) portrays a threat to us in several ways: It imposes uncertainty and a lack of control and reminds us of our own mortality. People around the world have reacted to these threats in seemingly unrelated ways: From stockpiling yeast and toilet paper to favoring nationalist ideas or endorsing conspiratorial beliefs. According to the General Process Model of Threat and Defense, the confrontation with a threat – a discrepant experience – makes humans react with both proximal and distal threat responses. While the proximal response manifests in behavioral inhibition that leads to heightened anxious arousal and vigilance, distal responses seek to lower behavioral inhibition and the associated state of anxiety and vigilance through engaging in distal defenses. In the present research, we propose that the reactions to COVID-19 may represent distal defense strategies to the pandemic and, therefore, can be explained and forecasted by the model. Thus, we hypothesized increased perceived COVID-19 threat to lead to a proximal threat response in the form of heightened behavioral inhibition. This, in return, should enhance the use of distal defenses (i.e., several ingroup biases, system justification, and conspiratorial beliefs) overlapping with the reactions observed as a response to COVID-19. This hypothesized mediated effect of increased perceived COVID-19 threat on distal defenses was tested in two preregistered studies: In Study 1 (N = 358), results showed perceived COVID-19 threat to be related to behavioral inhibition and, in turn, to be associated with increased distal defenses (i.e., higher entitativity, control restoration motivation, passive party support). In Study 2 (N = 348), we manipulated COVID-19 threat salience and found results suggesting the distal defenses of ingroup entitativity, system justification, and conspiratorial beliefs to be mediated by the proximal threat response. The results of the present research hint toward a common mechanism through which the seemingly unrelated reactions to COVID-19 can be explained. The results might help to predict future behavior during the COVID-19 pandemic and to design measures to counteract the detrimental effects of the pandemic.